PERAN ORANG TUA DALAM PEMBENTUKAN KARAKTER TUMBUH KEMBANG ANAK USIA DINI PADA USIA 3 – 6 TAHUN - Khadijah Khadijah; Homsani Nasution; Nur’Aini Nur’Aini; Siti Rahma Dewi Siregar; Nurbaiti Nasution (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
This study aims to understand the role of parents in character formation in early childhood development between 3 and 6 years old. The method used is descriptive qualitative research with data collection techniques through interviews with three parents in the Kapten Jamil area, Bandar Selamat, Medan. The research findings indicate that there are three important roles of parents in shaping children's character: as educators of moral and religious values, as providers of encouragement and positive support, and as providers of a safe and supportive environment. The application of moral and religious values is carried out through habits and examples in daily life. Positive support and motivation are provided through praise, assistance, and guidance that encourage children to repeat good behavior. In addition, a safe and loving family environment plays a significant role in supporting children's emotional and social development. Therefore, active parental involvement is a key element in developing positive character in children during the early years, known as the golden period of development.